Pengembangan Instrumen Evaluasi Belajar via Ponsel pada Mata Kuliah Pendidikan Agama Islam - Dahri, Sahrul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
This research was conducted because of the gap between technological progress which was already very rapid, with the development of education which was required to be able to catch up and adapt to these technological advances, so as not to cause a lag in the education sector. One solution to catch up and adapt to technological advances is to apply the use of technology in the process of learning, testing and assessment, as in this study the researchers applied the use of technology to the assessment process. This research was encouraged by previous studies that examined the use of google forms in learning, but in previous studies not on Islamic religious education courses, so this research is considered different from previous research. The path taken is by making an instrument for assessing learning outcomes using mobile phones which will be applied to the process of assessing Islamic religious education courses. This study aims to develop the use of mobile phones in the assessment of students with online methods, especially the google form. The method used in this research is the research and development method. The results of this study illustrate that to use google form in student test assessment activities can be done by way of introduction, design, development and distribution.